The long-term effects of charity nurseries: Evidence from early 20th century New York - Philipp Ager; Viktor Malein (European Historical Economics Society (EHES), 2024)
The paper evaluates the long-run impact of charity nurseries for disadvantaged children in early 20th-century New York. Access to charity nurseries with kindergarten instruction raised children's years of education and reduced their likelihood of working in low-skilled jobs later in life. Instead, exposed children were more likely to work in jobs requiring higher cognitive and language skills. The effects were strongest for children from the most disadvantaged immigrant groups at that time. Our findings suggest that kindergarten instruction in charity nurseries helped immigrant children better understand teachers' instructions and learning materials which improved their economic outcomes in adulthood.
Keywords: I21; I26; J13; J15; N31; 330; Age of Mass Migration; Charity Nurseries; Child Care; Disadvantaged Children; Kindergarten Instruction; New York City